Figure 14 from: Saarela JM, Sokoloff PC, Gillespie LJ, Bull RD, Bennett BA, Ponomarenko S (2020) Vascular plants of Victoria Island (Northwest Territories and Nunavut, Canada): a specimen-based study of an Arctic flora. PhytoKeys 141: 1-330. https://doi.org/10.3897/phytokeys.141.48810 - Saarela, Jeffery M.; Sokoloff, Paul C.; Gillespie, Lynn J.; Bull, Roger D.; Bennett, Bruce A.; Ponomarenko, Serguei (Zenodo, 2022)
Figure 14 ACarex krausei habit, Gillespie et al. 9977BCarex krausei inflorescence, Gillespie et al. 8114CCarex marina habit DCarex marina habitat ECarex maritima habit, Johansen Bay, NU, 18 July 2008 FCarex membranacea inflorescence. Photos A, F by J.M. Saarela C, D by B.A. Bennett and B, E by R.D. Bull.